Republic of Kazakhstan : Technical Assistance Report-Risk-Based Supervision Pillar 2 Liquidity. - International Monetary Fund. Monetary and Capital Markets Department (Washington, D.C. : International Monetary Fund, 2022)
This virtual technical assistance (TA) mission assisted the Agency in strengthening liquidity elements of its risk-based supervisory framework. The mission focused on supporting the Agency with the development of internal supervisory methodology for the assessment of banks' ILAAP and setting individual Pillar 2 supervisory liquidity requirements and provided guidance on stress testing and sensitivity analysis through survival horizon analysis. The mission consisted of a combination of presentations, discussions, and trainings, including case studies, and covered the BCBS standards on liquidity risk and other jurisdictions' approaches for the assessment of ILAAP and the Pillar 2 liquidity supervisory review process. This mission should be seen in the context of previous three IMF TA missions which were held since September 2020.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: International Agreements and Observance; International Organizations; Monetary Policy; Kazakhstan, Republic of